Green Buying Behavior Using Theory of TPB in Online Shop in Medan City - Eka Dewi Setia Tarigan; Yuni Syah Putri; Hesti Sabrina (International Journal of Science, Technology & Management, 2021)
Awareness of environmental responsibility in order to build a sustainable business makes marketers realize the importance of nurturing green consumers. The community now realizes the importance of green purchasing behavior in order to realize responsible behavior to preserve the environment. In this new normal era, people also purchase green products online. The research uses the TPB (Theory of Planned Behavior) theory proposed by Ajzen. This study discusses how the behavior of green online shop consumers in Medan city. The variables in this study are green consumer behavior. variable attitude, subjective norm and perceived behavior control. In the new normal era, the questionnaire was distributed and answered via google form to 100 respondents. From the processing of multiple linear regression analysis, it was found that the variable attitude and subjective norm had a positive and significant effect on green consumer behavior, and the variable perceived behavior control had no effect on green consumer behavior on online shops in Medan.